2021
DOI: 10.1177/17539447211058892
|View full text |Cite
|
Sign up to set email alerts
|

Leading 20 drug–drug interactions, polypharmacy, and analysis of the nature of risk factors due to QT interval prolonging drug use and potentially inappropriate psychotropic use in elderly psychiatry outpatients

Abstract: Background: Psychotropic medications extend corrected QT (QTc) period in the electrocardiogram (ECG). Psychiatric patients exposed to ⩾1 psychotropic medication(s) represent a group with marked probability of drug-activated QTc-prolongation. Prolonged QTc interval in elderly patients (age > 60 years) is connected to greater risk of all-cause and coronary heart disease deaths. This study aimed at investigating pattern of utilization of QTc-interval protracting medications, QT-extending drug interactions, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 56 publications
4
20
3
Order By: Relevance
“…The most common psychiatric diagnoses in our study population were dementia, substance use disorders, depression, and delirium, which is comparable to other studies (26,29,30). Previous studies examined the frequency and significance of risk factors for QT c prolongation in psychiatric patients (21,23,24,31).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The most common psychiatric diagnoses in our study population were dementia, substance use disorders, depression, and delirium, which is comparable to other studies (26,29,30). Previous studies examined the frequency and significance of risk factors for QT c prolongation in psychiatric patients (21,23,24,31).…”
Section: Discussionsupporting
confidence: 91%
“…Different study designs, enrollment of both inpatients and outpatients, as well as different age profiles of the participants may serve as explanations for these discrepancies. To date, three studies investigated the characteristics of QT c prolongation in geriatric psychiatry (26)(27)(28). Dumontet et al (28) found that in a sample of 88 inpatients, 29.4% of men and 21.4% of women displayed QT c prolongation.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta‐analysis which was limited to drug–drug‐interactions (DDIs) leading to QT prolongation in psychiatric patients has estimated an incidence of 42% among the patients, and the factors age, polypharmacy, and comorbidity were significantly associated with the occurrence of potential QT drug DDIs 36 . Similarly, many other studies on the prevalence of QT drugs in older persons are limited to antipsychotic drugs or psychiatric patients 37 . In contrast, we conducted a very broad analysis including all QT drugs to follow‐up on our 2016 study.…”
Section: Discussionmentioning
confidence: 99%
“…Elderly patients are at a higher risk for polypharmacy, which is why Das et al have investigated medications with an impact on the QT interval, which relates to a higher risk of cardiovascular death and all-cause mortality ( 12 ). They identified that antidepressant, proton pump inhibitor, antipsychotic, antinausea, antimicrobial, and H2 receptor antagonist medications have highest interactions with inclination to toward QT-interval prolongation.…”
Section: Psychotropic Drug Interactionsmentioning
confidence: 99%
“…They identified that antidepressant, proton pump inhibitor, antipsychotic, antinausea, antimicrobial, and H2 receptor antagonist medications have highest interactions with inclination to toward QT-interval prolongation. They concluded that reliable evidence-based online drug knowledge resources, such as AzCERT/CredibleMeds Drug Lists, Medscape Drug Interactions Checker, Epocrates Online Interaction Check, and Drugs.com should be adopted to facilitate medication selection ( 12 ). A recent retrospective analysis conducted in 10 psychiatric hospitals in Germany has shown that 22,739 (83%) cases received 1–8 QT interval prolonging medications simultaneously, of which pipamperone, quetiapine, prothipendyl, and risperidone were the most common.…”
Section: Psychotropic Drug Interactionsmentioning
confidence: 99%